Evaluation of Postoperative Maturation of Brachiocephalic Arteriovenous Fistula in Chronic Kidney Disease Patients Using Doppler Ultrasonography - Fiska, Urmila; Habibie, Yopie Afriandi; Zakiaturrahmi, Zakiaturrahmi (Surgical Residency Program Syiah Kuala University, 2025)
Introduction: An arteriovenous fistula (AVF) is the preferred method of vascular access for patients with end-stage chronic kidney disease (CKD) undergoing hemodialysis. This study aimed to investigate whether there is a difference in the post-operative maturation of brachiocephalic AVFs at 6 weeks compared to 8 weeks in CKD patients, utilizing Doppler ultrasonography at RSUDZA Hospital. Methods: The study involved a sample of 16 patients who underwent brachiocephalic arteriovenous fistula (AVF) surgery at Zainoel Abidin General Hospital (RSUDZA) in Banda Aceh, between November 13 and December 14, 2023. This observational study utilized a prospective cohort design, and data analysis was performed using the Wilcoxon test, with a significance level set at p < 0.05. Results: The study found that most patients who underwent brachiocephalic arteriovenous fistula (AVF) procedures were women, particularly those aged between 56 and 65 years. Doppler ultrasonography was used to evaluate the patients at 6 and 8 weeks after the surgery. The results showed that 40% to 50% of patients had not met the maturation criteria set by KDOQI by the 6th week, and 30% to 40% still had not met these criteria by the 8th week. Conclusion: There is no significant difference in the post-operative maturation of brachiocephalic AVF for 6 weeks and 8 weeks in CKD patients using Doppler ultrasonography at RSUDZA hospital.